Modeling of demoralization in breast cancer - de Figueiredo, John M.; Kohn, Robert; Chung, Joyce Y.; Gostoli, Sara (Frontiers in Psychiatry, 2025)
ObjectiveThis study aimed at identifying correlates of demoralization in breast cancer.Materials and methodsInformation was obtained from outpatients with breast cancer at the Oncology Clinic of a university-affiliated hospital in the United States, using reliable and valid scales, and from the participants’ medical records on demographic and social characteristics, location, type, and stage of cancer, whether it was a re-occurrence or first time diagnosed, type of cancer treatment, medications being used, history of mental disorder, functional impairment, perceived stress, perceived social support, resilience, subjective incompetence, demoralization, and depression. Demoralization was measured with the Demoralization Scale. Bivariable and multivariable analyses were conducted with demoralization as the dependent variable.ResultsDemoralization correlated positively with functional impairment, perceived stress, depression, and subjective incompetence, and negatively with months since diagnosed with breast cancer, perceived social support, resilience, and quality of life. Forward stepwise regression conducted without depression in the regression equation identified emotional wellbeing subscale of quality of life, resilience, subjective incompetence, perceived social support, and functional impairment as significant. After forced entry of depression, perceived social support and mild depression ceased to be significant, leaving only moderate and severe depression as significant. Perceived stress did not enter any of the regression models.ConclusionEarly detection of demoralization and of the co-occurrence of depression and demoralization are essential for promoting the well-being of patients with breast cancer. Psychotherapy should focus on strengthening the modifiable negative correlates of demoralization, countering the modifiable positive correlates, and preventing the co-occurrence of demoralization and depression.